2017
DOI: 10.1002/imhj.21643
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Functioning and Personality Organization: Associations With Negative Maternal Behaviors

Abstract: The aim of this study was to examine whether mothers who manifest insensitive and disconnected behaviors in interaction with their infants differ in terms of maternal reflective functioning (RF), personality organization, and histories of abuse. A total of 86 mother-infant dyads, 28 of them with histories of abuse, participated in the study. RF was assessed with the Adult Attachment Interview (C. George, N. Kaplan, & M. Main, 1985), and personality organization was assessed with the self-report Inventory of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Kernberg's theoretical assumptions and model of personality functioning have been the object of empirical scrutiny in recent years, and the relationship between PO, psychopathology, and PDs more specifically has been empirically supported in both clinical and non‐clinical adult populations (Ellison & Levy, 2012; Ensink, Rousseau, Biberdzic, Bégin, & Normandin, 2017; Gagnon, Vintiloiu, & McDuff, 2016; Pilarska & Suchańska, 2016; Sollberger & Walter, 2010; Stern et al, 2010; Yun, Stern, Lenzenweger, & Tiersky, 2013), with the construct of PO being used to measure structural aspects of personality functioning (Fischer‐Kern et al, 2010; Koelen et al, 2012). For example, in a clinical sample of patients with BPD, Sollberger and Walter (2010) found that BPD patients with high identity diffusion showed significantly higher levels of psychiatric symptoms, as well as higher anxiety, anger, and depression scores compared to BPD patients with lower identity diffusion.…”
Section: Personality Organizationmentioning
confidence: 99%
“…Kernberg's theoretical assumptions and model of personality functioning have been the object of empirical scrutiny in recent years, and the relationship between PO, psychopathology, and PDs more specifically has been empirically supported in both clinical and non‐clinical adult populations (Ellison & Levy, 2012; Ensink, Rousseau, Biberdzic, Bégin, & Normandin, 2017; Gagnon, Vintiloiu, & McDuff, 2016; Pilarska & Suchańska, 2016; Sollberger & Walter, 2010; Stern et al, 2010; Yun, Stern, Lenzenweger, & Tiersky, 2013), with the construct of PO being used to measure structural aspects of personality functioning (Fischer‐Kern et al, 2010; Koelen et al, 2012). For example, in a clinical sample of patients with BPD, Sollberger and Walter (2010) found that BPD patients with high identity diffusion showed significantly higher levels of psychiatric symptoms, as well as higher anxiety, anger, and depression scores compared to BPD patients with lower identity diffusion.…”
Section: Personality Organizationmentioning
confidence: 99%
“…It includes the capacity to think about, understand, interpret, and predict one's own and others’ behavior. The concept of mentalizing is being intensively investigated in the context of motherhood and postpartum psychopathology (e.g., Bigelow et al., 2018; Cordes et al., 2017; Ensink et al., 2017; Marcoux et al., 2016; Pawlby et al., 2010; Suchman et al., 2010). Various concepts and methodologies of maternal mentalization exist.…”
Section: Introductionmentioning
confidence: 99%
“…Mentalizing has recently become more relevant in women suffering from mental disorders at postpartum. Its impairment negatively affects not only maternal caregiving but also the child's mental health (Ensink et al., 2016, 2017; Slade, 2005). This seems particularly important in the context of postpartum depression (PPD), which is highly prevalent in the first year following the child's birth.…”
Section: Introductionmentioning
confidence: 99%
“…However, CSA-exposure does not inevitably or always have negative implications for parenting. One study failed to find an association between CSA–exposure and parenting problems – working with a low risk community sample, Ensink and colleagues did not find evidence for an association between CSA-exposure and insensitive parenting (Ensink et al, 2017b) or disorganized infant attachment (Ensink et al, 2016c). However, CSA-exposed mothers report significantly more identity diffusion and primitive defenses, indicative of underlying risk mechanisms that may or may not manifest depending in their interaction with other risk factors.…”
Section: Introductionmentioning
confidence: 99%